2015
DOI: 10.1371/journal.pgen.1005576
|View full text |Cite
|
Sign up to set email alerts
|

The Gyc76C Receptor Guanylyl Cyclase and the Foraging cGMP-Dependent Kinase Regulate Extracellular Matrix Organization and BMP Signaling in the Developing Wing of Drosophila melanogaster

Abstract: The developing crossveins of the wing of Drosophila melanogaster are specified by long-range BMP signaling and are especially sensitive to loss of extracellular modulators of BMP signaling such as the Chordin homolog Short gastrulation (Sog). However, the role of the extracellular matrix in BMP signaling and Sog activity in the crossveins has been poorly explored. Using a genetic mosaic screen for mutations that disrupt BMP signaling and posterior crossvein development, we identify Gyc76C, a member of the rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 101 publications
1
4
0
Order By: Relevance
“…We also showed that Gyc76C is required during muscle development for proper localization of integrins at sites of contact between the body wall muscles and tendon cells [ 19 ]. Consistent with our demonstration of a role for gyc76C and for in integrin-dependent adhesion, recent studies in the developing wing show that gyc76C and for regulate ECM-remodeling matrix metalloproteinases [ 20 ]. Although we reported gyc76C to be expressed in the developing trachea [ 19 ], it was previously not known what role gyc76C played in tracheal development.…”
Section: Introductionsupporting
confidence: 90%
“…We also showed that Gyc76C is required during muscle development for proper localization of integrins at sites of contact between the body wall muscles and tendon cells [ 19 ]. Consistent with our demonstration of a role for gyc76C and for in integrin-dependent adhesion, recent studies in the developing wing show that gyc76C and for regulate ECM-remodeling matrix metalloproteinases [ 20 ]. Although we reported gyc76C to be expressed in the developing trachea [ 19 ], it was previously not known what role gyc76C played in tracheal development.…”
Section: Introductionsupporting
confidence: 90%
“…This suggests that FOR acts through Mav and Gbb to negatively regulate nerve terminal growth, although it remains possible that FOR functions in a parallel pathway to Mav and Gbb. Interestingly, FOR also regulates TGF-β/BMP signalling in the developing wing of Drosophila (Schleede and Blair, 2015). PKG regulates intracellular Ca 2+ levels in rat glial cell cultures (Willmott et al, 2000).…”
Section: Glial For Negatively Regulates Nerve Terminal Growth Throughmentioning
confidence: 99%
“…RNAi of Vg in insects such as Nilaparvata lugens [41], Bemisia tabaci [42], and Panonychus citri [43] can inhibit ovarian development and reduce egg production, while RNAi-mediated suppression of Vg expression in adult Cimex lectularius females drastically reduced egg production, and resulted in atrophied ovaries and an inflated abdomen caused by hypertrophied fat bodies [44]. In Drosophila, GCY is associated with memory and embryonic cell development [45][46][47]. In C. elegans, GCY is also involved in body development, but more reports have focused on neural mechanisms [20,21].…”
Section: Discussionmentioning
confidence: 99%